Germany’s national security strategy in the context of Zeitenwende - Michał M. Kosman (Świat Idei i Polityki)
The article examines German foreign and security policy in response to the Russian invasion of Ukraine in February 2022. The study aims to track Germany’s reaction to the conflict in Eastern Europe, which prompted significant changes in its foreign policy due to the deteriorating security situation on the continent. This shift, highlighted by Chancellor Olaf Scholz’s speech three days after the Russian military operations began, became known as Zeitenwende. The analysis covers political, military, and economic aspects. Additionally, the article discusses the German National Security Strategy, adopted in June 2023, which addresses the new security environment and is the first document of its kind in Germany’s history. The study employs document analysis and literature review in both German and Polish.